The Level of Maternal Knowledge about Complications in Pregnancy toward the Increase of Low Birth Weight Cases - Aisyah Apriliciciliana Aryani; Besral Besral (Disease Prevention and Public Health Journal, 2020)
Background: Based on Metro City Health Office reports, there was an increase in the proportion of LBW cases from 75 cases per 1.000 live births in 2015 to 87 cases per 1.000 live births in 2016. Metro City Health Service stated that one of the causes was the low level of maternal knowledge, especially regarding the consumption of balanced nutrition during pregnancy. This study aimed to investigate the relationship between the level of maternal knowledge and Low Birth Weight (LBW). Method: The study design was case-control, where low birth weight as a case and normal weight as a control. Study sample was 102, consisting of 51 cases and 51 control. Dependent variable was low birth weight, independent variable was the level of maternal knowledge. Data was obtained by interviewing the mothers, and secondary data was collected from community health center records. Data was analysed by bivariate and multivariate analysis. Results: Bivariate analysis showed that the OR level of maternal knowledge was 2,598 (95% CI: 1,126-5,995). The results of multivariate analysis showed that OR level of maternal knowledge was 2,646 (95% CI: 1,092-6,410). Conclusion: Mother's level of knowledge is a risk factor for LBW in Metro City.